Learning Technology in Teaching: A Research on Implementation of Technology at Islamic Educational Institutions in Indonesia - Ritonga, Mahyudin; Hasibuan, Kalijunjung; Ritonga, Syaipuddin; ., Julhadi (International Journal of Membrane Science and Technology, 2023)
Technological developments become a challenge for education to continue to improve the quality of learning. Indonesian Islamic education must also respond and apply technology as an improvement in education and to prepare quality graduates. Therefore, this study aims to look at Islamic educational institutions in responding to technological developments in the current era. So this study used a quantitative design with a survey method with a total sample of 86 respondents from 86 different Islamic educational institutions. Samples were taken randomly using the technique cluster random sampling and convenience sampling. Data analysis uses descriptive statistics which describe the entirety of the respondents' answers. Based on the findings and analysis, two important aspects can be concluded, namely: 1) the use of technology in Islamic education is currently comprehensive, this is evidenced that the percentage of survey results shows above 80% of institutions have implemented technology in their institutions. Of course, this technology has been designed to improve students' abilities both from cognitive, affective, and psychomotor aspects. Not only that, 21st century capabilities are also involved in designing the applied technology, namely 4C, critical thinking, creativity, collaboration, and communication. 2). The curriculum is also designed using existing technology, so that its application can make it easier for both teachers as instructors and students as learners. 80% of institutions have also implemented it. Another thing that became this finding, the institution also provides facilities for teachers to continue to improve their competence both in curriculum development and in the use of technology.